Strategi Peningkatan Kemampuan SDM Pelaku Wisata Alam dan Eksistensi Pendidikan Agama Islam - Imron Fauzi; Aminulloh (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2021)
This study aims to analyze the strategies undertaken to improve the ability of human resources of natural tourism actors Ijen Crater, the implications of these strategies for the continuity of natural tourism activities Ijen Crater, as well as the existence of Islamic religious education in improving the ability of human resources of natural tourism actors. The method used is qualitative. Informants included Mount Ijen Volcanology Officers, Mount Ijen Forest Police, Tourism Activists, Tourists, Tourism Service Providers, Traders, Muslim Leaders or figures, Local Communities, and the Tourism Office. Data collection techniques used interviews, observation, and documentary studies. Data analysis covered stages: data condensation, display, and conclusion drawing/verifications. Data validity uses triangulation and extended participation methods. The results of this study are that the tourism potential is quite adequate to improve the ability of human resources of tourism actors, especially in the local community, to limited understanding of language, tourism insights, and networking, the opportunities are not optimal and taken over by people from outside the Regency. Although the district government has programmed a series of tourism training, there is still an imbalance in the distribution of the regional budget, which is only disbursed for and prioritizes the district government's tourism assets and for the benefit of bureaucrats. Therefore, the strategy has not had a significant impact on improving the ability of human resources of tourism actors compared to the big name of KWA Ijen and the budget provided for the continuity of tourism activities. The values of Islamic religious education are applied in various forms of culture, indicating that the pattern of teaching Islam addition to being obtained from the educational institution is obtained from the implementation of existing rituals and traditions that have become norms in the community.